Clarification of some morphological characters in Artemisia anomala (Asteraceae, Anthemideae), with reduction of var. tomentella and var. acuminatissima to the synonymy of the species - Guo, Xin-Qiang; Wang, Long; Yang, Qin-Er (Phytotaxa, 2021)
Based on observations on herbarium specimens (including type material) and living plants in the wild, we demonstrate that Artemisia anomala (Asteraceae, Anthemideae), a distinctive Chinese species yet morphologically imperfectly understood since its description, is variable with respect to its leaf indumentum and shape within and between populations. The leaves are ovate, ovate-lanceolate, elliptic-lanceolate, or lanceolate, and adaxially sparsely pubescent or glabrous, abaxially tomentose to sparsely pubescent, or rarely glabrescent. Morphologically, the two currently recognized varieties of A. anomala, var. tomentella and var. acuminatissima, fall within the variation range of the species in leaf indumentum and shape, and thus are synonymized herein. Lectotypification is proposed for A. anomala.